Τhe implementation of an interactive educational intervention program using the Kinems learning games platform to improve gross motor skills in children with ASD - Farsari, Eleftheria; Nitsiou, Chrisa (Preschool and Primary Education, 2025)
Introduction: Autism spectrum disorder (ASD) is a developmental disorder that simultaneously affects several areas of development such as communication, cognition, socialization, and movement, causing at the same time stereotyped behavior to occur. Purpose of the study: The purpose of this study was to investigate the use of interactive educational games as part of an educational program to enhance gross motor development of primary school students with ASD. Method: In this two-phases study, a case-control design was applied using a 3-month interactive educational platform based intervention with 15 children with ASD, while a similar control group of 16 children with ASD followed their schools’ typical teaching methods. The mean age of the children was 9.2 ± 1.4 years old and the groups were adjusted for gender, age, body type and dominant foot or leg. During the first phase of the study, and before the beginning of the intervention, children’s gross mobility was measured using the latest version of the Test of Gross Motor Development TGMD (version 3.0.). Then, the intervention was conducted using a selected list of games from the interactive educational platform named Kinems. During the second phase of the study, children’s gross mobility was measured again, using the Test of Gross Motor Development-3. Results: The gross mobility scales, the TGMD-3 scores, showed significant differences in children in the intervention group compared to the children in the control group, specifically regarding two of the TGMD-3 skills, namely ‘gallop’ and ‘2-hand catch’ scores. In most of the thirteen activities studied, children in the intervention group showed higher mean differences compared to the children in the control group. %Mean Success score was corelated with equivalent ages based on Locomotor skills. Implications & conclusions: The findings suggest that the interactive educational intervention program applied with primary school children with ASD, had a positive effect in their gross motor skills.